[Rezension von: Baden, Joel S., 1977-, The book of Exodus : a biography] - Byrd, James P. (Church history, 2021)
//static.cambridge.org/content/id/urn%3Acambridge.org%3Aid%3Aarticle%3AS0009640721001220/resource/name/firstPage-S0009640721001220a.jpg